Male-mediated spontaneous abortion among spouses of stainless steel welders - Hjollund, NHI; Bonde, Jens Peter E; Kold Jensen, T; Brink Henriksen, T; Andersson, A-M; Kolstad, Henrik A; Ernst, E; Giwercman, A; Skakkebæk, Niels Erik; Olsen, Jørn (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'Male-mediated spontaneous abortion has never been documented for humans. The welding of stainless steel is associated with the pulmonary absorption of hexavalent chromium, which has genotoxic effects on germ cells in rodents. Clinical and early subclinical spontaneous abortions were examined among spouses of stainless-steel welders.' ' METHODS ': 'A cohort of first-pregnancy planners was recruited from members of the union of metal workers and 3 other trade unions. The cohort was followed for 6 menstrual cycles from the cessation of contraceptive use. Altogether, 280 pregnancies were conceived, of which 35 were detected by human chorionic gonadotrophic hormone analysis and did not survive to a clinically recognized pregnancy. Information on exposure was collected prospectively in relation to the outcome and was available for all cycles resulting in a pregnancy. Information on pregnancy outcome was collected for all 245 clinically recognized pregnancies.' ' RESULTS ': 'Increased risk of spontaneous abortion was found for pregnancies with exposure to paternal stainless-steel welding (adjusted relative risk 3.5, 95% confidence interval 1.3-9.1). The results were consistent in analyses of both biochemically and clinically recognized abortions. There was no increased risk for spontaneous abortion in pregnancies with paternal exposure to the welding of metals other than stainless steel.' ' CONCLUSION ': 'Male welding of stainless steel was associated with an increased risk of spontaneous abortion in spouses. A mutagenic effect of hexavalent chromium has been found previously in both somatic and germ cells, and the findings could be due to mutations in the male genome.
Keywords: chromium; embryonal loss; follow-up study; male; mediated spontaneous abortion; metals; mutagenicity; occupation; spouse; stainless steel welder